Platinum-based drugs and hydrogel: a promising anti-tumor combination - Jiamin Yao; Shaojuan Song; Hang Zhao; Yao Yuan (Taylor & Francis Group, 2023)
AbstractPlatinum-based drugs are widely used as first-line anti-tumor chemotherapy agents. However, they also have nonnegligible side effects due to the free drugs in circulation. Therefore, it is necessary to develop efficient and safe delivery systems for better tumor cell targeting. Hydrogel is a promising anti-tumor drug carrier that can form a platinum/hydrogel combination system for drug release, which has shown better anti-tumor effects in some studies. However, there is a lack of systematic summary in this field. This review aims to provide a comprehensive overview of the platinum/hydrogel combination system with the following sections: firstly, an introduction of platinum-based drugs; secondly, an analysis of the platinum/hydrogel combination system; and thirdly, a discussion of the advantages of the hydrogel-based delivery system. We hope this review can offer some insights for the development of the platinum/hydrogel combination system for better cancer therapy.